Ectopic expression of N‐acetylglucosaminyltransferase V accelerates hepatic triglyceride synthesis. Issue 3 (14th July 2015) - Kamada, Yoshihiro; Ebisutani, Yusuke; Kida, Sachiho; Mizutani, Kayo; Akita, Maaya; Yamamoto, Akiko; Fujii, Hironobu; Sobajima, Tomoaki; Terao, Naoko; Takamatsu, Shinji; Yoshida, Yuichi; Takehara, Tetsuo; et al.
Abstract : Aim: Glycosylation changes induce various types of biological phenomena in human diseases. N ‐Acetylglucosaminyltransferase V (GnT‐V) is one of the most important glycosyltransferases involved in cancer biology. Recently, many researchers have challenged studies of lipid metabolism in cancer. To elucidate the relationships between cancer and lipid metabolism more precisely, we investigated the effects of GnT‐V on lipid metabolism. In this study, we investigated the effects of aberrant glycosylation by GnT‐V on hepatic triglyceride production. Methods: We compared lipid metabolism in GnT‐V transgenic (Tg) mice with that of wild‐type (WT) mice fed with normal chow or a choline‐deficient amino acid‐defined (CDAA) diet in vivo . HepG2 cells and GnT‐V transfectants of Hep3B cells were used in an in vitro study. Results: Serum triglyceride levels and hepatic very low‐density lipoprotein (VLDL) secretion in Tg mice were significantly elevated compared with that of WT mice. Hepatic lipogenic genes ( Lxrα, Srebp1, Fas and Acc ) and VLDL secretion‐related gene ( Mttp1 ) were significantly higher in Tg mice. Expression of these genes was also significantly higher in GnT‐V transfectants than in mock cells. Knockdown of GnT‐V decreased, while both epidermal growth factor and transforming growth factor‐β1 stimulation increased LXRα gene expression in HepG2 cells. Finally, we found that the blockade of VLDL secretion by CDAA diet induced massive hepatic steatosis in Tg mice. Conclusion: Our study demonstrates that enhancement of hepatic GnT‐V activity accelerates triglyceride synthesis and VLDL secretion. Glycosylation modification by GnT‐V regulation could be a novel target for a therapeutic approach to lipid metabolism.